2015
DOI: 10.1186/s12885-015-1258-1
|View full text |Cite
|
Sign up to set email alerts
|

Changing the clinical course of glioma patients by preoperative motor mapping with navigated transcranial magnetic brain stimulation

Abstract: BackgroundMapping of the motor cortex by navigated transcranial magnetic stimulation (nTMS) can be used for preoperative planning in brain tumor patients. Just recently, it has been proven to actually change outcomes by increasing the rate of gross total resection (GTR) and by reducing the surgery-related rate of paresis significantly in cohorts of patients suffering from different entities of intracranial lesions. Yet, we also need data that shows whether these changes also lead to a changed clinical course, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…The EOR that we observed in this study is in accordance with other studies on the effect of mapping on EOR (24, 2325). Studies have shown conclusively that IOM results in greater EOR (6, 23, 26); how the addition of preoperative mapping further improves EOR is not as obvious.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The EOR that we observed in this study is in accordance with other studies on the effect of mapping on EOR (24, 2325). Studies have shown conclusively that IOM results in greater EOR (6, 23, 26); how the addition of preoperative mapping further improves EOR is not as obvious.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, having preoperative nTMS data allowed for limited craniotomy size because larger exposures simply for mapping purposes were not required (6). Prior comparisons between large cohorts of patients undergoing nTMS and non-nTMS (for various primary CNS pathologies including eloquent gliomas) were not able to show any significant difference in surgical time (24). We postulate that this difference is due to the infiltrative nature of gliomas—in these cases, surgeons depend on IOM to give the most complete resection of abnormal tissue within eloquent cortex.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations